Good practices on reducing food waste throughout the food supply chain - Mirela Stanciu; Agatha Popescu; Iuliana Antonie; Camelia Sava; Bogdan Gabriel Nistoreanu (Amfiteatru Economic Journal, 2022)
Research to identify initiatives to reduce food waste (FW) in Romania is quite limited, and existing studies at the European and international level have highlighted the need to promote models of good practice that can be multiplied on a large scale. In this context, the aim of the paper is to highlight good practices for preventing and reducing food waste in the EU and in Romania, so that different organizations and decision makers can develop better interventions in this regard. The best practices for preventing and reducing FW identified and presented in the paper refer to: the use of digital technology, projects and platforms, organizations involved in volunteering, food banks, mobile applications, social innovation, corporate social entrepreneurship, education, and public awareness. The paper also identified the determinants of food waste, encountered at the end of the food supply chain FSC (Food Supply Chain), as well as good practices to prevent and reduce it, to make it available to organizations, authorities, and households a wide range of models that can be implemented internationally and in Romania as well.
Keywords: F53; Q13; Q18; Q58; 330; best practices; EU; food supply chain; food waste; Romania